Language and power dynamics: A critical policy analysis of racial and choice discourses in school integration policies - Diem, Sarah; Good, Madeline; Smotherson, Brittany; Walters, Sarah W.; Bonney, Vida Nana Ama (Education Policy Analysis Archives, 2022)
Although school segregation has been illegal for nearly seven decades, it persists in a public education context increasingly impacted by market-based ideologies. Indeed, many present-day school integration policies are having to negotiate school choice while simultaneously trying to serve the public good. Through a critical policy analysis (CPA) of three policies in school districts with distinct histories of integration efforts, we examine these tensions by exploring how racial discourses are factors in contemporary school integration policies and how discourses of choice uphold or disrupt existing racial inequities. In our CPA, we pair Critical Discourse Analysis and interest divergence to better understand power behind and within discourse, and how discourses of race and school choice illustrate new but perhaps reminiscent shifts toward interest divergence. In doing so, we show how policies themselves cannot be disentangled from the rhetoric, power, accountability, and politics surrounding their development and implementation.